PERKEMBANGAN SOSIAL EMOSIONAL ANAK PRA SEKOLAH DENGAN INSTRUMEN KUESIONER MASALAH MENTAL EMOSIONAL - Emsya Salsabela; Siti Khumaeroh; Rr Deni Widjayatri (Abata : Jurnal Pendidikan Islam Anak Usia Dini, 2022)
The period of social emotional development of pre-school children needs to be monitored as early as possible with the emotional mental problem questionnaire (KMME) instrument tool useful for early detection in emotional deviations that can be carried out on children aged 36-72 months, namely the pre-school period. The purpose of this study to provide knowledge about the social-emotional development aged 36-72 months of pre-school children. This research activity was carried out at KB Ar-Raudho Serang using descriptive qualitative methods with interview techniques using the KMME instrument. Doing this KMME is useful for parents to know the social emotional development of children by knowing if the child has or does not have emotional problems. The results of the survey, was found from the number of informants 15 children in KB Ar-Raudho Serang there were 6 children who had good emotional abilities, 2 children had an answer of 1 "Yes" and for 8 other children according to the KMME instrument if more than 2 " YES”, it is possible that the child has mental problems, and the educator can only do KMME and direct parents to check their children to mental health facilities or child development, without diagnosing mental problems the child has.